Evaluation of white matter myelin water fraction in chronic stroke() - Borich, M.R. (Elsevier, 2013)
Multi-component T(2) relaxation imaging (MCRI) provides specific in vivo measurement of myelin water content and tissue water environments through myelin water fraction (MWF), intra/extra-cellular water fraction (I/EWF) and intra/extracellular and global geometric mean T(2) (GMT(2)) times. Quantitative MCRI assessment of tissue water environments has provided new insights into the progression and underlying white matter pathology in neural disorders such as multiple sclerosis. It has not previously been applied to investigate changes in white matter in the stroke-affected brain. Thus, the purposes of this study were to 1) use MCRI to index myelin water content and tissue water environments in the brain after stroke 2) evaluate relationships between MWF and diffusion behavior indexed by diffusion tensor imaging-based metrics and 3) examine the relationship between white matter status (MWF and fractional anisotropy) and motor behavior in the chronic phase of stroke recovery. Twenty individuals with ischemic stroke and 12 matched healthy controls participated. Excellent to good test/re-test and inter-rater reliability was observed for region of interest-based voxelwise MWF data. Reduced MWF was observed in whole-cerebrum white matter (p < 0.001) and in the ipsilesional (p = 0.017) and contralesional (p = 0.037) posterior limb of internal capsule (PLIC) after stroke compared to whole-cerebrum and bilateral PLIC MWF in healthy controls. The stroke group also demonstrated increased I/EWF, I/E GMT(2) and global GMT(2) times for whole-cerebrum white matter. Measures of diffusion behavior were also significantly different in the stroke group across each region investigated (p < 0.001). MWF was not significantly correlated with specific tensor-based measures of diffusion in the PLIC for either group. Fractional anisotropy in the ipsilesional PLIC correlated with motor behavior in chronic stroke. These results provide novel insights into tissue-specific changes within white matter after stroke that may have important applications for the understanding of the neuropathology of stroke.